Serum lactate levels and perfusion index: are these prognostic factors on mortality and morbidity in very low-birth weight infants?. (3rd May 2017) - Tuten, Abdulhamit; Dincer, Emre; Topcuoglu, Sevilay; Sancak, Selim; Akar, Selahattin; Hakyemez Toptan, Handan; Özalkaya, Elif; Gokmen, Tulin; Ovalı, Fahri; Karatekin, Guner
Abstract: Aim : Early hemodynamic assessment of global parameters in critically ill newborns fails and requires mostly invasive measurements in neonatal intensive care unit. Clinical signs are frequently used for assessment of peripheral perfusion. Perfusion index (PI) is a new noninvasive numerical value of peripheral perfusion. Serum lactate levels and PI are the indicators that are important in determining prognosis of preterm infants. In this study, we aimed to investigate the relationship of serum lactate levels and PI with mortality and morbidity in very low-birth weight infants (VLBW). Study design : This study was conducted between July 2014 and July 2015 in a Level III NICU. The study enrolled preterm infants with a gestational age ≤ 32 weeks, birth weight ≤ 1500 g. Serum lactate levels from blood gases and PI, SpO2 measurements were recorded at 1st, 12th and 24th hours by using a new generation pulse-oximeter. Morbidities and mortalities were documented. Results : A total of 60 VLBW infants were enrolled the study. Mean birth weight and gestational age were 991 ± 288 g and 27.5 ± 2.5 w, respectively. Retinopathy of prematurity (ROP) was significantly higher in the patients with high lactate levels (>4 mg/dl) at 1st hour and low-PI levels (<0.5) at 12th hour of life ( p = 0.042, p = 0.015), respectively. Bronchopulmonary displasia (BPD) was significantly higher in the patients with low PI (< 0.5) at 1st hour. Lactate and PI values were not significantly correlated with necrotizing enterocolitis, intraventricular hemorrhage, patent ductus arteriosus, sepsis and mortality. Conclusion : High lactate levels (> 4 mg/dl) and low PI (< 0.5) could be used as early parameters for prediction of ROP and BPD. This data suggests that in VLBW infants lactate levels and PI parameters during the first 24 h will be effective in determining the prognosis of the disease. We believe that larger, randomized controlled clinical trials are likely to establish the true benefit.